Pembelajaran Kolaboratif Berbasis Lesson Study Menggunakan Model Guided Inquiry di MTS Laboratorium Kota Jambi - Haerul Pathoni; Nova Susanti (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2016)
Based on the observation do in MTS Laboratorium Kota Jambi, many of the content of physics learning should be taught with practical or use of instructional media done not because many of factors. It is because of practical limitations of the tools or ÃÂ no advanced media available . It ÃÂ would not be allowed , its solution must be sought in order to study physics can be do ÃÂ accordance with the curriculum indicator. This research offers a solution with collaborative learning based on lesson study using model guided inqury. Lesson study do in MTS Laboratorium Kota Jambi increased from 90 % to 100 % in the first cycle and 66.67 % completing ÃÂ in the second cycleÃÂ